2018
DOI: 10.3390/toxins10040167
|View full text |Cite
|
Sign up to set email alerts
|

Solid Phase Adsorption Toxin Tracking (SPATT) Technology for the Monitoring of Aquatic Toxins: A Review

Abstract: The Solid Phase Adsorption Toxin Tracking (SPATT) technology, first introduced in 2004, uses porous synthetic resins capable of passively adsorbing toxins produced by harmful microalgae or cyanobacteria and dissolved in the water. This method allows for the detection of toxic compounds directly in the water column and offers numerous advantages over current monitoring techniques (e.g., shellfish or fish testing and microalgae/cyanobacteria cell detection), despite some limitations. Numerous laboratory and fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 135 publications
(248 reference statements)
0
19
0
Order By: Relevance
“…Rats and mice are common animal models for toxicological studies in mammals. Previous studies reported consistent conclusions to support the nephrotoxicity of MCs in rats [19,20,[24][25][26][27][28][29][30][31][32][33][34][35], but had different views on mice in terms of whether MCs could injure mouse kidneys. Qin, studying the toxicity of MC-LR in mice, found negative outcomes for the kidney, though they did not exclude possible endoplasmic reticulum stress (EMS) in kidney cells [26].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Rats and mice are common animal models for toxicological studies in mammals. Previous studies reported consistent conclusions to support the nephrotoxicity of MCs in rats [19,20,[24][25][26][27][28][29][30][31][32][33][34][35], but had different views on mice in terms of whether MCs could injure mouse kidneys. Qin, studying the toxicity of MC-LR in mice, found negative outcomes for the kidney, though they did not exclude possible endoplasmic reticulum stress (EMS) in kidney cells [26].…”
Section: Introductionmentioning
confidence: 91%
“…Over the past decades, most research has been focused on MC-LR and relatively little on MC-RR. These two analogues are cyclic heptapeptides that differ in one amino acid at two variable L-amino acid units (X and Y), MC-LR with a leucine and MC-RR with an arginine respectively [ 32 ]. This chemical differentiation results in differences in their nature and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…grab samples) provide only a snapshot (in space and time) and may miss areas or times of highest occurrence and therefore risk. To overcome these challenges, the use of solid‐phase adsorption toxin tracking (SPATT) samplers has been applied (Miller et al., 2010; Roué, Darius, & Chinain, 2018; Wood, Holland, & MacKenzie, 2011). This method allows toxins dissolved in the water to bind to an absorbent material suspended in fine mesh.…”
Section: Monitoring Sampling and Sample Analysismentioning
confidence: 99%
“…But according to a previous report 24 , under some conditions, POCIS may result in inaccurate estimations of organic compound concentrations. SPATT also presents some limitations, such as a lack of calibration (no optimal deployment time), thereby limiting the more widespread adoption of this technology for monitoringof pollutants 25 . The DGT technology was developed by Davison and Zhang 26 and initially was used to detect trace metals in natural fresh water systems 20 .…”
Section: Introductionmentioning
confidence: 99%